Fear of Infection, Motivation, and Rewards Related to Health Cadres Performance in Tuberculosis Case Detection - Hermanto, Raden Bagus Bambang; Lailatul K, Marlina Fitriya; Sendewana, Elis Anugrah Wati; Manggasa, Dafrosia Darmi (Madago Nursing Journal, 2025)
Background: Indonesia remains one of the countries with the highest tuberculosis (TB) burden globally. In Poso District, the 2023 Case Detection Rate (CDR) reached only 65.87%, still below the national target of 75%. Low case detection contributes to delayed diagnosis, persistent community transmission, and failure to reach TB elimination targets. Objective: To analyze factors associated with the performance of health cadres in detecting TB cases in the working area of Tagolu Primary Health Center, Poso District. Methods: This descriptive cross-sectional study involved all active health cadres (n=52) selected through total sampling. Data were collected using validated structured questionnaires. Variables included fear of infection, stigma, motivation, rewards, and cadre performance. Data were analyzed using descriptive statistics and Chi-square tests with a significance level of α = 0.05. Results: Three variables were significantly associated with cadre performance: fear of TB transmission (p = 0.024), motivation (p = 0.004), and rewards (p = 0.039). Stigma was not significantly associated (p = 0.579). Most cadres had high fear of infection (63.5%), low motivation (57.7%), and perceived rewards as adequate (69.2%). A total of 61.5% demonstrated good performance in TB case detection. Conclusion: Fear of infection, motivation, and rewards are significant determinants of cadre performance in TB case detection. Improving protective equipment availability, strengthening training, and implementing sustainable reward mechanisms are essential to enhance early TB detection in the community